Exploring the concept of cultural divinity in supporting religious moderation in Indonesia - Andi Suhardiyanto; Tutik Wijayanti; Hendri Irawan (Jurnal Civics: Media Kajian Kewarganegaraan)
As a diverse nation, Indonesia often experiences clashes regarding diversity in life. The culturally embedded concept of divinity is believed to be a driving force in supporting religious moderation in Indonesia. This concept is crucial in religious pluralism in Indonesia, a country with diverse cultural and religious backgrounds. This study adopts a qualitative approach through a literature review referencing national and international journals indexed in Scopus. The research findings indicate that maintaining harmony among religious communities and religious moderation serves as a strong foundation. Culturally embedded divinity refers to understanding cultural and religious diversity, a noble heritage of the Indonesian nation. Through this understanding, it is hoped that society can appreciate differences and strengthen tolerance among religious communities. This article also explores the implementation of culturally embedded divinity in public policies, efforts to enhance interfaith dialogue in Indonesia, and the public perception of moderate attitudes. The research trend on religious moderation in Indonesia is still very low. Thus, it is concluded that a profound understanding of this concept can strengthen the foundation of religious harmony and unity amidst Indonesia's diversity.